Cost-benefit studies of natural resource management in Southeast Asia - James, D. E. (David Edward), 1942-; Francisco, Herminia Arocena- (Singapore : Springer, 2015)
'This book applies cost-benefit analysis techniques in the management of environment and natural resources in developing countries of the Southeast Asian region and presents a compendium of studies conducted by researchers supported by the Economy and Environment Program for Southeast Asia (EEPSEA). It emphasizes the close relationship between the environment and natural resources and economic development in such countries, addressing a wide range of problems that can be understood using economic evaluation techniques. General guidelines for conducting economic appraisals are provided, with the case studies illustrating how they can be applied in a developing country context. Cost-Benefit Analysis Application in Environmental and Natural Resource Management in Southeast Asia serves as essential reading for teachers, researchers, students and practitioners in environmental and natural resource economics, economic development and key issues facing policymakers in the Southeast Asian region'--Provided by publisher.
Part I. Guide to cost-benefit analysis and case studies -- Part II. Agriculture, forestry and fisheries -- Part III. River basin management -- Part IV. Protected areas -- Part V. Adaptation to climate change.
Includes bibliographical references and index.
Keywords: Natural resources -- Southeast Asia -- Management -- Cost effectiveness